Effects of statins on coronary and peripheral endothelial function in humans: a systematic review and meta-analysis of randomized controlled trials - Martin Reriani; Shannon M. Dunlay; Bhanu Gupta; Colin P. West; Charanjit S. Rihal; Lilach O. Lerman; Amir Lerman (2011)
The purpose of this study was to quantify the effect of statins on peripheral and coronary endothelial function in patients with and without established cardiovascular disease. Early atherosclerosis is characterized by endothelial dysfunction, a known prognostic factor for cardiovascular disease. The search included MEDLINE, Cochrane Library, Scopus, and EMBASE to identify studies up to 1 December 2009. Eligible studies were randomized controlled trials on the effects of statins compared with placebo on endothelial function. Two reviewers extracted data on study characteristics, methods, and outcomes. Forty-six eligible trials enrolled a total of 2706 patients: 866 (32%) were women and 432 (16%) had established cardiovascular disease. Meta-analysis using random-effects models showed treatment with statins significantly improved endothelial function [standardized mean difference (SMD) 0.66, 95% CI 0.46–0.85, p < 0.001]. Subgroup analyses demonstrated statistically significant improvement in endothelial function assessed both peripherally by flow-mediated dilatation (SMD 0.68, 95% CI 0.46–0.90, p < 0.001) and venous occlusion plethysmography (SMD 0.59, 95% CI 0.06–1.13, p = 0.03) and centrally in the coronary circulation by infusion of acetylcholine (SMD 1.58, 95% CI 0.31–2.84, p = 0.01). Significant heterogeneity observed across studies was explained in part by the type of endothelial function measurement, statin type and dose, and study population differences. Exclusion of outlier studies did not significantly alter the results. Statin therapy is associated with significant improvement in both peripheral and coronary endothelial function. The current study supports a role for statin therapy in patients with endothelial dysfunction.